Pengaruh Fluktuasi Harga, Biaya Produksi dan Akses Pasar Terhadap Pendapatan Petani Cengkeh di Kecamatan Boawae Kabupaten Nagekeo - Alfridus Mau Manek; Pedro Gonzales Rae; Hermanus Haba (MAMEN: Jurnal Manajemen, 2026)
access on farmers' income in Boawae District, Nagekeo Regency. The purpose of this study was to determine the influence of price fluctuations, production costs and market access on farmers' income in Boawae District, Nagekeo Regency. The data used are primary data collected through interviews with clove farmers and observations and questionnaire results. Based on the results of Multiple Linear Regression Analysis, it can be seen that the t-test results for the price fluctuation variable have t count = 2.554> t table = 1.996564 and a sig. value of 0.013 <0.05, meaning that the price fluctuation variable has a positive and significant effect on the income of clove farmers in Boawae District. While the production cost variable has t count = 2.262> 1.996564 and a sig. value of 0.027 <0.05, meaning that the production cost variable has a positive and significant effect on the income of clove farmers. Furthermore, the market access variable has a calculated t-value of -2.360 > t-table = 1.996564 and a sig. value of 0.021 < 0.05. This means that market access has a significant effect on income, but in a negative direction. This means that when market access increases, farmer income decreases. Based on the F-test results, the calculated F-value is 6.888 > f-table = 2.744 and a sig. value of 0.000 < 0.05, indicating that price fluctuations, production costs, and market access simultaneously influence the income of clove farmers in Boawae District, Nagekeo Regency.